ENZYME ACTIVITY IN RELATION TO TOTAL K, Ca, Mg, Fe, Cu AND Zn IN THE OIL PALM RHIZOSPHERE OF RIAU’S PEATLANDS, INDONESIA - Mimien Harianti; Atang Sutandi; Rasti Saraswati; Maswar Maswar; Supiandi Sabiham (BIOTROPIA, 2018)
Enzyme activity can be used as an indicator of peat decomposition in the oil palm rhizosphere of peatlands. Oil palm plantation management requires fertilization in the rhizosphere to provide nutrients for oil palm growth. The state of total nutrients in the rhizosphere can influence enzyme activity. This research aimed to study enzyme activity in relation to nutrient content in the oil palm rhizosphere of peatlands. Using the explorative method in Riau's tropical peatlands, an oil palm plantation was chosen as the main site, and a degraded forest as well as a shrubland were chosen as comparison sites. In the oil palm plantation, peat samples were taken from peat adhering to oil palm roots at depths of 0–25 and 25–50 cm and at distances of 0–1, 1–2, 2–3, and 3–4 m from the trees. In the degraded forest and shrubland, samples were taken from selected plant roots at depths of 0–25 and 25–50 cm. The triplicate peat samples were then composited for analysis of enzyme activity and total nutrient content. Results showed that enzyme activity (urease, phosphatase, β-glucosidase, and laccase) in the oil palm rhizosphere decreased as the distance from trees and the depth of the rhizosphere increased. The decline in enzyme activity was caused by low peat pH and increased water content as well as organic carbon content. Enzyme activity increased with increasing oil palm age and ash content. Total K and Zn contents showed no correlation with enzyme activities. However, total Ca and Mg contents showed a positive correlation only with β-glucosidase activity. Total Fe and Cu contents showed a significantly negative correlation with enzyme activities (urease, phosphatase, β-glucosidase, and laccase). Enzyme activity in the rhizosphere of the degraded forest and shrubland was mostly lower than in the oil palm rhizosphere.